Effects of Conduction Variation on MHD Natural Convection Flow along a Vertical Flat Plate with Thermal Conductivity (Journal of Scientific Research, 2016)
This paper reports the effect of conduction variation of free convection flow along a vertical flat plate on magnetohydrodynamic (MHD) with thermal conductivity. The governing equations with associated boundary conditions reduce to local non-similarity boundary layer equations for this phenomenon are converted to dimensionless forms using a suitable transformation. The transformed non-linear equations are then solved using the implicit finite difference method together with Keller-box technique. Numerical results of the velocity and temperature profiles, skin friction and surface temperature profiles for different values of the magnetic parameter, the thermal conductivity variation parameter, the Prandtl number and the conduction variation parameters are presented graphically. Detailed discussion is given for the effect of the aforementioned parameters. Opposite scenario is found in skin friction and surface temperature for the thermal conductivity variation parameter. Significant effect is found in skin friction and surface temperature for conduction variation parameter.